Agro-industrial Development in Lamongan District, East Java, Indonesia - Ajeng Nugrahaning Dewanti; Jayant Kumar Routray; Rima Dewi (IPTEK Journal of Proceedings Series, 2014)
Lamongan District has considerable potential in the agricultural sector. However, the agricultural sector has not been able to generate added value in the regional development of Lamongan Regency. The high GDP of agriculture sector is not matched with the high GDP of industrial sector. This proves that the results of the agricultural sector has not been used optimally by the industrial sector. To increase the value added of industrial sectors, it would require agro-industrial development based on predominant crops in Lamongan District. The potential area based on agricultural situation and the current status of agro-industrial development is required to provide the strategy of agro-industrial development.  The study of current situation of agriculture sector was conducted with three analysis namely agriculture efficiency analysis, location quotient analysis, and shift share analysis. Whereas, the study of current status of agro-industrial development was conducted with descriptive analysis. Furthermore, identification of potential areas was based on the classification of the area using the quartile method which distinguishes the area (sub-district) into four classes namely very low potential, low potential, medium potential and high potential. After identifying the level of agricultural potential, the current level of agro-industrial development was studied based on selected indicators. Following two sets of analyses, the potential sub-districts have been identified for intensification of agro-industrial development relating to predominant crops. In the study, few sub-districts such as Brondong, Deket and Glagah have high potential for agro-industrial development.